2022
DOI: 10.3389/fmicb.2022.842623
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of Bacillus pseudomycoides Chromate Transporter Increases Chromate Tolerance in Bacillus subtilis

Abstract: Chromium of anthropogenic origin contaminates the environment worldwide. The toxicity of chromium, a group I human carcinogen, is greatest when it is in a hexavalent oxidation state, Cr(VI). Cr(VI) is actively transported into the cell, triggering oxidative damage intracellularly. Due to the abundance of unspecific intracellular reductants, any microbial species is capable of bio-transformation of toxic Cr(VI) to innocuous Cr(III), however, this process is often lethal. Only some bacterial species are capable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Everted membrane vesicles of Pseudomonas aeruginosa PAO1 expressing ChrA accumulated more CrO4 2– than those of plasmid-free cells, indicating the functions of the chromate efflux system in the Cr-resistant strain . Implantation of Bacillus pseudomycoides chromate transporter protein increases chromium efflux from Bacillus subtilis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Everted membrane vesicles of Pseudomonas aeruginosa PAO1 expressing ChrA accumulated more CrO4 2– than those of plasmid-free cells, indicating the functions of the chromate efflux system in the Cr-resistant strain . Implantation of Bacillus pseudomycoides chromate transporter protein increases chromium efflux from Bacillus subtilis …”
Section: Introductionmentioning
confidence: 99%
“…19 Implantation of Bacillus pseudomycoides chromate transporter protein increases chromium efflux from Bacillus subtilis. 20 Microbial Cr(VI) reduction currently faces a critical challenge that only a minimal proportion of microbes has Cr(VI) reduction and resistance capability in a natural soil environment, causing a prolonged period for remediation. 21 Bioaugmentation or biostimulation is therefore introduced to solve these problems by introducing Cr-stabilizing and Crreducing strains or substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike its trivalent form (Cr 3+ ), hexavalent chromium (Cr 6+ ) poses a serious environmental problem (Fu et al, 2021 ; Lara et al, 2021 ; Wang et al, 2022 ; Aguilar et al, 2023 ; Mohanty et al, 2023 ) and triggers harmful effects that make its elimination essential (Wang et al, 2021 ; Aké et al, 2022 ; Alharbi et al, 2022 ). Moreover, Cr 6+ is found to be particularly hazardous to health (Tangahu et al, 2020 ; Aparicio et al, 2021 ) and responsible for dysfunction in living organisms (Tripathi et al, 2018 ; Chromikova et al, 2022 ). Hence, Cr 6+ removal has become the focus of attention in health and safety projects (Tumolo et al, 2020 ; Anupong et al, 2022 ; Ariram et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides adsorption on the cell surface, chromium can penetrate the microbial cell through sulfate and phosphate transporters ( , ), and Cr 6+ can undergo enzymatic or non-enzymatic reduction (indirect reduction) inside the cell (Thatoi et al, 2014 ). The ability of microorganisms to adsorb Cr 6+ and Cr 3+ was also demonstrated using scanning electron microscopy (SEM) combined to energy dispersive X-ray spectroscopy (EDX) (Abo-Alkasem et al, 2022 ; Chromikova et al, 2022 ). At high concentrations, the authors found cellular modifications due to high Cr 6+ concentrations (Abo-Alkasem et al, 2022 ; Chromikova et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation